HUBUNGAN SIKAP BELAJAR DENGAN HASIL BELAJAR MAHASISWA JURUSAN KTP FIP UNP DALAM MATA KULIAH KOMPUTER GRAFIS - Meldi Ade Kurnia yusri (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
This research was motivated by the low student learning outcome at Curriculum and Technology of Education in Education of Sciences Faculty, State University of Padang. The purpose of this research was to reveal the relationship of learning attitudes with learning outcome of student TM 2013 semester 2 in KTP FIP UNP majors. This research used quantitative methods to the type of correlational research. The sample in this research were 77 students TM 2013 semester 2 in KTP FIP UNP majors, used Slovin formula with proportional random sampling technique. The research instrument was structured in the form of a questionnaire with Likert scale models, after being tested looking for validity and reliability. The data were analyzed using simple linear regression. The results showed that There was a significant positive relationship between the attitude of learning with learning outcome of students TM 2013 semesters 2 in Curriculum and Educational Technology majors by 0,646. Based on the findings of this study concluded that the independent variables, namely learning attitude played a very important in improving learning outcome, in addition to other variables.